Preparation and characterization of ultra-high-strength and ultra-high-ductility cementitious composites incorporating waste clay brick powder. (20th August 2021) - Wu, Jian-Dong; Guo, Li-Ping; Qin, Yao-Yi
Abstract: Large quantities of waste clay bricks from construction and demolition (C&D) waste are currently stockpiled in landﬁlls, which is an environmentally, technically, and economically detrimental procedure. In this work, waste clay bricks powder (WCBP) was assessed to determine its feasibility as an alternative to cement for ultra-high-strength and ultra-high ductility cementitious composites (UHS-UHDCCs). The influences of WCBP on the fluidity, hydration, mechanical properties, fiber/matrix interface performances, autogenous shrinkage, and ecological overload capacity of UHS-UHDCC with different replacement levels ranging from 0 to 50% were investigated. The results indicate that WCBPs reduce the fluidity of the UHS-UHDCC matrix. WCBP content of 20% slightly accelerates the hydration process and exhibits the highest compressive and flexural strength in the specimens. Moreover, all UHS-UHDCCs achieve strain-hardening characteristics and exhibit a tensile strain capacity of 3.18–5.47%. UHS-UHDCC with 20% WCBP obtains excellent ultimate tensile stress and tensile strain capability, reaching around 9.34 MPa and 3.18%, respectively. The performance of the interface frictional bond ( τ ) with different WCBP content was obtained through single-fiber pullout tests, which reasonably explained the macroscopic tensile properties of UHS-UHDCC. The average interface frictional bond ( τ ) between the fiber and matrix of UHS-UHDCC reaches the maximum 1.72 MPa in the WCBP20 specimen. The average slip hardening coefficient ( β ) of UHS-UHDCC is distributed between 0.0031 and 0.0075 and tends to be excellent in the WCBP20 specimen. The theoretical fiber bridging stress vs crack displacement relationship of UHS-UHDCC was calculated through the limitation of interface parameters, which had an excellent correlation with the experimental results. Furthermore, the introduction of WCBP remarkably reduces the autogenous shrinkage of UHS-UHDCC. The ecological overload capacity of UHS-UHDCC is decreased by the introduction of WCBP, which provides an environmentally friendly solution for the C&D and cement industries.